To study the performance of polyaniline-based copper and carbon-nanotube (PANI@Cu@CNT) nanocomposite for harmful NH3 gas sensing - Shah Masheerul Aalam; Aaliyah Farooq; Mohd Sarvar; Mohd Nadeem Bhat; Monika Tomar; Mohammad Moeen Hasan Raza; Javid Ali (Scientific Reports)
Abstract This study examined a room temperature operative, highly sensitive, stable, and selective PANI ammonia (NH3) gas sensor using multiwalled carbon nanotubes (MWCNTs) and copper nanocomposites (Cu). The silicon substrate was coated with the sensing materials using the drop casting technique. To synthesize PANI, PANI@Cu@MWCNT nanocomposites chemical polymerisation method and ultrasonication techniques were used. In comparison to three PANI nano-composite sensor, which demonstrated sensing responses of 18%, 28%, and 43%, respectively, the PANI@Cu3@MWCNT3-based sensor demonstrated a greater sensing response of 116% under the room temperature conditions of NH3 (100 ppm). The resistance variation of all the sensors is 62 kΩ, 78 kΩ, 89 kΩ, and 90 kΩ respectively. The PANI@Cu3@MWCNT3 based sensor exhibited excellent results in term of resistance (90 kΩ). The stability, response time (10 s), and recovery time (13 s) of PANI@Cu2@MWCNT2 is measured and has better results in terms of time than all other sensors. Pure PANI nano-composite sensor has shown the sensing response of 18%, resistance variation of 62 kΩ, response time (45 s), recovery time (48 s) respectively. The sensing materials were characterized using FTIR, XRD, EDX, and FESEM techniques. PANI and PANI@Cu@MWCNT nanocomposites’ gas sensing capabilities were examined using a Keithley 6514 multimeter.